1977
DOI: 10.2514/3.58830
|View full text |Cite
|
Sign up to set email alerts
|

Core Noise Measurements on a YF-102 Turbofan Engine

Abstract: Core noise from a YF-102 high bypass ratio turbofan engine was investigated through the use of simultaneous measurements of internal fluctuating pressures and far field noise. Acoustic waveguide probes, located in the engine at the compressor exit, in the combustor, at the turbine exit, and in the core na4zle, were employed to measure internal fluctuating pressures. Spectra showed that the internal signals were free of tones, except at high frequency where machinery noise was present. Data obtained over a wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Since in-flight effects reduce jet noise more than combustion noise, combustion noise can be a significant contributor to aircraft approach noise but masked by jet noise under the corresponding static-engine test condition. To overcome this obstacle, researchers [4][5][6][7][8][9][10][11][12][13] developed coherence techniques utilizing engine-internal as well as far-field measurements to identify the far-field combustion noise component. Modal analyses [14][15][16][17] were also carried out to determine the source and propagation characteristics of combustion noise.…”
Section: Nasa Sti Program In Profi Lementioning
confidence: 99%
“…Since in-flight effects reduce jet noise more than combustion noise, combustion noise can be a significant contributor to aircraft approach noise but masked by jet noise under the corresponding static-engine test condition. To overcome this obstacle, researchers [4][5][6][7][8][9][10][11][12][13] developed coherence techniques utilizing engine-internal as well as far-field measurements to identify the far-field combustion noise component. Modal analyses [14][15][16][17] were also carried out to determine the source and propagation characteristics of combustion noise.…”
Section: Nasa Sti Program In Profi Lementioning
confidence: 99%
“…(25) is expressed in terms of four onedimensional normal modes with wave numbers given by Eqs. (35) to (37). Equations (36) and (37) (42) is very large and this wave is highly damped for the cases considered herein.…”
Section: Analytical Model Governing Equationsmentioning
confidence: 93%
“…He concluded that the basic source generating mechanism is relatively smooth and somewhat featureless, but that the annular geometry of the combustor is extremely effective in modifying the unsteady pressure spectrum in the combustor. Karchmer 24 also carried out limited comparisons with existing far-field results 11 from an YF102 turbofan engine and found rough similarities between his isolated-component results and the full-engine measurements.…”
Section: Combustor Modal Analysismentioning
confidence: 99%
“…Since flight effects reduce jet noise more than combustor noise, combustor noise can be a significant contributor to aircraft in-flight noise but may be masked by jet noise under the corresponding static-engine test conditions. To overcome this obstacle, researchers [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] developed coherence techniques utilizing engine-internal, as well as far-field, measurements to identify the far-field combustor-noise component. Modal analyses [24][25][26][27][28][29] were also carried out to determine the source and propagation characteristics of combustor noise.…”
Section: Nasa Sti Program In Profi Lementioning
confidence: 99%